ENGLISH GRADUATE STUDENT’S PERCEPTION ABOUT THE EFFECTIVENESS OF ONLINE LEARNING TUTOR IN DISTANCE EDUCATION - Fauzy Rahman Kosasih; Juhana Juhana; Zulmi Ramdani; Lidwina Felisima Tae (University of Kuningan, 2023)
One of the successes of a learning program is obtained by the various feedbacks during the evaluation process, including when the program is implemented in the form of distance learning. The purpose of this study was to examine the perception of graduate students in English Education department about the effectiveness of distance learning carried out by the tutors during the learning process. Descriptive quantitative method was used in this study to answer the objectives of this study. A total of 21 students of master's degree in English Education department were involved in this study by selecting the respondents using the purposive sampling technique. The researchers used the measurement with reference to Kirkpatrick's model which explains the effectiveness of online learning through the aspects of reaction, learning, behavior and results. The result showed that the majority of respondents were satisfied with the learning process provided by the tutor as seen from the satisfaction score that reached more than 75% for each aspect. Meanwhile, other results also showed that the four aspects which were the manifestation of the effectiveness of a tutor's learning have a strong and significant relationship in supporting the performance of a tutor. This study emphasized the importance of elaboration of every aspect that must be possessed by the tutors in carrying out online learning.